Triggering events with GPUs at ATLAS. Issue 9 (December 2015) - Kama, S; Soares, J Augusto; Baines, J; Bauce, M; Bold, T; Muino, P Conde; Emeliyanov, D; Goncalo, R; Messina, A; Negrini, M; Rinaldi, L; Sidoti, A; et al.
Abstract: The growing complexity of events produced in LHC collisions demands increasing computing power both for the online selection and for the offline reconstruction of events. In recent years there have been significant advances in the performance of Graphics Processing Units (GPUs) both in terms of increased compute power and reduced power consumption that make GPUs extremely attractive for use in a complex particle physics experiments such as ATLAS. A small scale prototype of the full ATLAS High Level Trigger has been implemented that exploits reconstruction algorithms optimized for this new massively parallel paradigm. We discuss the integration procedure followed for this prototype and present the performance achieved and the prospects for the future.